Improving intercultural competencies in high school students: An educational intervention in a Peruvian region - Cucho Leyva, María Patricia (2025)
An objective of the study was to examine the effect of the educational intervention based on the situated learning approach on intercultural competence among 14 to 15-year-old secondary school students in the Loreto region of Peru in 2022. To this end, we sought to improve knowledge, attitudes, and skills on intercultural competence. The methodology used was mixed; in the first phase, a quasi-experiment was conducted, in the second phase the students' experiences and perceptions of the process of applying the intervention program were explored, and in the third phase the data were integrated. A situational test and an interview guide were used to collect numerical and verbal data. The results indicated that there was a statistically significant difference between the control and experimental groups and the effect was moderate in terms of intercultural competence. These quantitative results were supported by the verbal information obtained through the interviews. In conclusion, the results of this study support the effectiveness of the situated learning-based intervention program as they showed statistically significant improvements in knowledge, skills, and attitudes of high school students in the Loreto region of Peru, and the size of the effect showed a positive effect on these dimensions, including increased knowledge of different cultures, increased empathy, increased intercultural dialogue, and increased tolerance of cultural differences.